2022
DOI: 10.1155/2022/7531190
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of Infertility Factors Caused by Gynecological Chronic Pelvic Inflammation Disease Based on Multivariate Regression Analysis of Logistic

Abstract: In order to solve the complex and recurrent problem of chronic pelvic inflammation disease (CPID) in the process of the clinical treatment, a method of understanding the influencing factors of CPID by investigating the actual situation of clinical cases and using logistics regression analysis was proposed in this study. A total of 204 outpatients were selected from a certain hospital. The ratio of the cases in the experimental group to those in the control group stands at 1 : 1. The results were obtained as fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…Відсутність ефективних протимікробних препаратів може створити підвищену загрозу успіхам сучасної медицини у лікуванні інфекцій, у тому числі під час виконання складних хірургічних операцій та проведення хіміотерапії онкологічних захворювань [15]. До прикладу, значна поширеність та стійкість форм бактеріального вагінозу є причиною хронічних захворювань репродуктивних органів та передумовою 33% випадків жіночого безпліддя [16][17][18].…”
unclassified